Pitfalls in histone propionylation during bottom‐up mass spectrometry analysis - Meert, Paulien (Proteomics, 2015)
Despite their important role in regulating gene expression, posttranslational histone modifications remain technically challenging to analyze. For identification by bottom‐up MS, propionylation is required prior to and following trypsin digestion. Hereby, more hydrophobic peptides are generated enabling RP HPLC separation. When histone dynamics are studied in a quantitative manner, specificity, and efficiency of this chemical derivatization are crucial. Therefore we examined eight different protocols, including two different propionylation reagents. This revealed amidation (up to 70%) and methylation (up to 9%) of carboxyl groups as a side reaction. Moreover, incomplete (up to 85%) as well as a specific propionylation (up to 63%) can occur, depending on the protocol. These results highlight the possible pitfalls and implications for data analysis when doing bottom‐up MS on histones.